Ultrasound Biomicroscopy Comparison of Ab Interno and Ab Externo Intraocular Lens Scleral Fixation - Horiguchi, Lie (J Ophthalmol, 2016)
Purpose. To compare ab interno and ab externo scleral fixation of posterior chamber intraocular lenses (PCIOL) using ultrasound biomicroscopy (UBM). Methods. Randomized patients underwent ab externo or ab interno scleral fixation of a PCIOL. Ultrasound biomicroscopy was performed 3 to 6 months postoperatively, to determine PCIOL centration, IOL distance to the iris at 12, 3, 6, and 9 hours, and haptics placement in relation to the ciliary sulcus. Results. Fifteen patients were enrolled in the study. The ab externo technique was used in 7 eyes (46.6%) and the ab interno in 8 eyes (53.3%). In the ab externo technique, 14 haptics were located: 4 (28.57%) in the ciliary sulcus; 2 (14.28%) anterior to the sulcus; and 8 (57.14%) posterior to the sulcus, 6 in the ciliary body and 2 posterior to the ciliary body. In the ab interno group, 4 haptics (25.0%) were in the ciliary sulcus, 2 (12.50%) anterior to the sulcus, and 10 (75.0%) posterior to the sulcus, 4 in the ciliary body and 6 posterior to the ciliary body. Conclusions. Ab externo and ab interno scleral fixation techniques presented similar results in haptic placement. Ab externo technique presented higher vertical tilt when compared to the ab interno.